Freedom from emotional eating - McKenna, Paul, 1963- (Hay House, Inc., 2015)
"Emotional eating is the number-one cause of obesity in the Western world. In a society that fails to meet our human needs, millions of people medicate themselves with second-best solutions--drinking, drugs, shopping, and the Western drug of choice: eating. But Paul McKenna has cracked the code! "Just when I thought there was nothing more to learn about weight loss, I have discovered the most amazing breakthrough ever," says Dr. McKenna. "It's the fastest, safest, most powerful way ever to change the systemic imbalances that cause overeating. This breakthrough will change what you eat, improve how you feel, and massively increase your success in every area of your life." This amazing new system gets beneath the issue of weight loss to eradicate the root cause of overeating. The program in this book, with downloadable video and audio NLP and guided hypnosis techniques, brings about dynamic, lasting change--a gentle breakthrough that transforms your body, your relationship to food, and your entire life one day at a time to bring you freedom, success, and a sense of security and joy that is currently beyond what you can imagine. Paul McKenna can help overweight people escape from the unsatisfying cycle of frustration and self-medication with food. He can help them find the inner strength to feel confident and happy so they can stop being taken advantage of by the hate-your-body diet industry and feel an inner sense of peace, comfort, and control even in the most challenging situations"--